Mobile Application with Augmented Reality as a Tool to Reinforce Learning in Pre-Inca Cultures - Cabanillas-Carbonell, Michael (2020)
Peru is one of the countries with the most rich and varied culture in the world, which can be made known by making use of augmented reality for better understanding and learning at school. This document shows the development of an application following the mobile d methodology, for the creation of 3D models regarding pre-Inca cultures and determines the influence it would have on the learning of students at the primary level. Using the quasi-experimental design, the sample consists of 84 students from the third grade divided into 2 classrooms (control group and experimental group). The results show an increase of 33.07% in grades, 49.51% in satisfaction, 42.85% in motivation and a reduction of 34.05% in evaluation time with respect to the post-test, applied to the experimental group.